(3x-2)/5=(2x-1)/4

Simple and best practice solution for (3x-2)/5=(2x-1)/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2)/5=(2x-1)/4 equation:


x in (-oo:+oo)

(3*x-2)/5 = (2*x-1)/4 // - (2*x-1)/4

(3*x-2)/5-((2*x-1)/4) = 0

(3*x-2)/5+(-1*(2*x-1))/4 = 0

(4*(3*x-2))/(4*5)+(-1*5*(2*x-1))/(4*5) = 0

4*(3*x-2)-1*5*(2*x-1) = 0

2*x-3 = 0

(2*x-3)/(4*5) = 0

(2*x-3)/(4*5) = 0 // * 4*5

2*x-3 = 0

2*x-3 = 0 // + 3

2*x = 3 // : 2

x = 3/2

x = 3/2

See similar equations:

| 2x/3+y/5=0 | | c-8=-17 | | -9d=36 | | 2(x+5)=9x+2-7x+8 | | -(x-6)-6x=-8x+3(-x-6) | | 9x+3=2x+52 | | A+2b/4+4a | | 5(x+4)=2x+29 | | 2q^2+75/2=-20q | | x^4+x=1 | | -8+t=-6 | | X^2=3X-4 | | 4x^5/6x^-3 | | -4(k-1)=10-6k | | 4x^5/6x-3 | | 0=-10x^2+3500x-66000 | | 2d^2+4d-13=0 | | 3=11+4n | | 4x(-2)=12 | | log(6)(x)-log(6)(x+1)=2 | | 14x+3=0 | | y-0.2=0.6(y+3) | | (7x^2+5x/x^2+1)-(5x/x^2-6)=0 | | 1.4=0.3x+1/2*4x^2 | | 2=7+5a | | 7x+14=8x-10 | | -(w+0.2)=0.6(y+3) | | 2.25=a/740 | | 12.62*10.2*2= | | ((7x^2+5x)/(x^2+1))-((5x)/(x^2-6)) | | 2Y^3-2Y=0 | | 12x+30=-6 |

Equations solver categories